International Consensus Statement on Allergy and Rhinology: Rhinosinusitis. (18th February 2016) - Orlandi, Richard R.; Kingdom, Todd T.; Hwang, Peter H.; Smith, Timothy L.; Alt, Jeremiah A.; Baroody, Fuad M.; Batra, Pete S.; Bernal‐Sprekelsen, Manuel; Bhattacharyya, Neil; Chandra, Rakesh K.; Chiu, Alexander; Citardi, Martin J.; et al.
Abstract : Contributing Authors: Isam Alobid, MD, PhD 1, Nithin D. Adappa, MD 2, Henry P. Barham, MD 3, Thiago Bezerra, MD 4, Nadieska Caballero, MD 5, Eugene G. Chang, MD 6, Gaurav Chawdhary, MD 7, Philip Chen, MD 8, John P. Dahl, MD, PhD 9, Anthony Del Signore, MD 10, Carrie Flanagan, MD 11, Daniel N. Frank, PhD 12, Kai Fruth, MD, PhD 13, Anne Getz, MD 14, Samuel Greig, MD 15, Elisa A. Illing, MD 16, David W. Jang, MD 17, Yong Gi Jung, MD 18, Sammy Khalili, MD, MSc 19, Cristobal Langdon, MD 20, Kent Lam, MD 21, Stella Lee, MD 22, Seth Lieberman, MD 23, Patricia Loftus, MD 24, Luis Macias‐Valle, MD 25, R. Peter Manes, MD 26, Jill Mazza, MD 27, Leandra Mfuna, MD 28, David Morrissey, MD 29, Sue Jean Mun, MD 30, Jonathan B. Overdevest, MD, PhD 31, Jayant M. Pinto, MD 32, Jain Ravi, MD 33, Douglas Reh, MD 34, Peta L. Sacks, MD 35, Michael H. Saste, MD 36, John Schneider, MD, MA 37, Ahmad R. Sedaghat, MD, PhD 38, Zachary M. Soler, MD 39, Neville Teo, MD 40, Kota Wada, MD 41, Kevin Welch, MD 42, Troy D. Woodard, MD 43, Alan Workman 44, Yi Chen Zhao, MD 45, David Zopf, MD 46 Contributing Author Affiliations: 1 Universidad de Barcelona; 2 University of Pennsylvania; 3 Louisiana State University Health Sciences Center; 4 Universidade de São Paulo; 5 ENT Specialists of Illinois; 6 University of Arizona; 7 University of Oxford; 8 University of Texas; 9 University of Indiana; 10 Mount Sinai Beth Israel; 11 Emory University; 12 University of Colorado; 13 Wiesbaden, Germany; 14 University of Colorado; 15 University of Alberta; 16 University of Alabama at Birmingham; 17 Duke University; 18 Sungkyunkwan University; 19 University of Pennsylvania; 20 Universidad de Barcelona; 21 Northwestern University; 22 University of Pittsburgh; 23 New York University; 24 Emory University; 25 University of British Columbia; 26 Yale University School of Medicine; 27 Private Practice; 28 Department of Otolaryngology, Hôtel‐Dieu Hospital, Centre de Recherche du Centre Hospitalier de l'Université de Montréal; 29 University of Adelaide; 30 Pusan National University; 31 University of California, San Francisco; 32 University of Chicago; 33 University of Auckland; 34 Johns Hopkins University; 35 University of New South Wales, Australia; 36 Stanford University; 37 Washington University; 38 Harvard Medical School; 39 Medical University of South Carolina; 40 Singapore General Hospital; 41 Taho University; 42 Northwestern University; 43 Cleveland Clinic Foundation; 44 University of Pennsylvania; 45 University of Adelaide; 46 University of Michigan